2004
DOI: 10.1590/s1516-14392004000100009
|View full text |Cite
|
Sign up to set email alerts
|

High temperature corrosion in gasifiers

Abstract: Several commercial scale coal gasification combined cycle power plants have been built and successfully operated during the last 5-10 years. Supporting research on materials of construction has been carried out for the last 20 years by EPRI and others. Emphasis was on metallic alloys for heat exchangers and other components in contact with hot corrosive gases at high temperatures. In this paper major high temperature corrosion mechanisms, materials performance in presently operating gasifiers and future resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In atmospheres with low levels of chlorine reported from metal parts of the syngas cooler in coal fired gasifiers, stainless steels with at least 20 wt% chromium typically exhibit a mixed outer (Fe,Cr,Ni)S layer and an inner oxide layer with some sulphur content closest to the metal/scale interface [1]. Metal loss was reported to be below 0.1 mm/year at 300-400 8C [1]. In the present case, internal attack was observed, but the outer layer consisted of zinc sulphide, which is an important difference.…”
Section: Corrosion Performance and Comparison With Literature On Coalmentioning
confidence: 99%
“…In atmospheres with low levels of chlorine reported from metal parts of the syngas cooler in coal fired gasifiers, stainless steels with at least 20 wt% chromium typically exhibit a mixed outer (Fe,Cr,Ni)S layer and an inner oxide layer with some sulphur content closest to the metal/scale interface [1]. Metal loss was reported to be below 0.1 mm/year at 300-400 8C [1]. In the present case, internal attack was observed, but the outer layer consisted of zinc sulphide, which is an important difference.…”
Section: Corrosion Performance and Comparison With Literature On Coalmentioning
confidence: 99%
“…These components not only form initial fouling layer, but also contribute to poisoning of COS-hydrolysis catalyst [14]. Besides chlorides, H2S formed from sulfur species during gasification is not only corrosive to syngas cooler [14,114] but can also contribute to the strengthening the deposit by reacting with very fine iron particles to form pyrrhotite [115].…”
Section: Foulingmentioning
confidence: 99%
“…21,22 It was an unpleasant surprise, since the MPC autoclave tests had suggested that many materials would survive if the temperature was dropped to below 750uC. However, most of the early work in America and Europe seems not to have taken into account the fact that many coals contain significant amounts of chlorine.…”
Section: Superheater Materials For Igcc Systemsmentioning
confidence: 99%
“…Bakker points out that HCl could affect the corrosion rate directly by migrating down cracks in scales consisting of various Fe, Ni and Cr sulphides, which are themselves not very protective, then forming a layer of FeCl 2 at the interface. 21 As in waste incineration plants, Bakker considered that there was some potential for a reflux mechanism to build up the levels FeCl 2 in the scale. If liquid or vapour chloride migrates back outwards through the scale, steam could react with FeCl 2 , thereby increasing the local concentration of HCl and increasing the rate of attack.…”
Section: Superheater Materials For Igcc Systemsmentioning
confidence: 99%